Polar bears and expanding sea ice in the Mid Holocene Aleutian Islands, Alaska - Lillian Draper Parker; Catherine F. West; Kaylee Hope Tatum; Michael Etnier; Brandi Bethke; Katherine Reedy; Nikkita Shellikoff; Courtney A. Hofman (Scientific Reports, 2025)
Abstract The archaeological record offers the opportunity to infer the effects of regional climatic shifts on species distributions and human-animal interactions. In Alaska’s temperate Aleutian Islands, the archaeological record suggests that the Neoglacial climate phase (ca. 4700 − 2500 rcyr BP) was significantly colder and the region likely supported sea ice and ice-dependent animals. Previous analyses have identified polar bear (Ursus maritimus) remains in archaeological sites in Unalaska Bay, which have been used to infer bear range expansion and significant climate changes during this period. However, morphological similarities between polar and brown (Ursus arctos) bears make it difficult to distinguish between the two species, and the presence of bear material in Unalaska Bay could be the result of long-distance travel or trade rather than local harvest. Here, we applied zooarchaeological methods to address potential morphological and size differences, to age the bears, and to interpret human use of the bears. Our results suggest that the small assemblage is likely composed of both brown and polar bear remains, but that morphological analyses alone are insufficient to definitively reconstruct bear distributions in this context. Bear age profiles and butchery patterns suggest that the animals were harvested locally and the extension of sea ice in the Neoglacial phase likely facilitated their presence around Unalaska Island. Future analyses that use ancient DNA, collagen fingerprinting, and stable isotopes to determine the species, sex, number of individuals, and relationships to modern populations will be necessary to illuminate regional bear population dynamics in the Neoglacial.